La paridad, alternancia de género y evolución del rol de la mujer en la escena política y gestión pública en el Perú - Casanova Mera, Gina Valeria (2023)
The article focuses on discussing the parity and alternation of women within the political scene and national public management, considering the globalization of the design and implementation of public policies in the last twen-ty-five years, in favor of equal rights and equal rights. gender, in all its aspects. This has led the States to adapt their legislation and public policies to allow greater representation and participation of women in public tasks, granting them a greater share of power and decision-making within the public office that they have to perform within the national sphere. In this sense, a reference is made to the current situation and how it has evolved and how much progress still has to be made.